Law and social transformation in India - Mendelsohn, Oliver (New Delhi, 2014)
This work uncovers the historical roots and also the contemporary character of law and society in India. Steeped in years of fieldwork in both rural and urban India the work places the new legal forces and processes introduced into India by the British alongside those that predated the colonial incursion and still have vitality today.
Keywords: Sociological jurisprudence-India